1993
DOI: 10.1002/j.1460-2075.1993.tb05680.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimer formation of cJun and ATF-2 is responsible for induction of c-jun by the 243 amino acid adenovirus E1A protein.

Abstract: The adenovirus E1A proteins differentially regulate AP‐1‐responsive genes. Collagenase and stromelysin are repressed by E1A, whereas the expression of c‐jun is elevated. Inhibition of collagenase has been found to be exerted through the consensus AP‐1 binding site TGAGTCA. Here we show that the distal AP‐1 binding site in the c‐jun promoter, the jun2TRE (TTACCTCA), is the decisive element of this promoter in mediating the positive response to the 243 amino acid E1A product. In vitro binding studies revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
261
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(270 citation statements)
references
References 43 publications
9
261
0
Order By: Relevance
“…Our finding provided evidence for an alternative mechanism whereby CREB was phosphorylated by MAPKs as found by Yu et al (51). ATF-2 has been reported to be activated by JNK and p38 (52,53). In this study, we showed that ATF-2 was activated by all three MAPKs.…”
Section: Discussionsupporting
confidence: 82%
“…Our finding provided evidence for an alternative mechanism whereby CREB was phosphorylated by MAPKs as found by Yu et al (51). ATF-2 has been reported to be activated by JNK and p38 (52,53). In this study, we showed that ATF-2 was activated by all three MAPKs.…”
Section: Discussionsupporting
confidence: 82%
“…Expression of dnJun has no effect on either basal AP-1 activity (1, 2) or on the enzyme activity of JNK (data not shown) but does inhibit phosphorylation-dependent activation of transcription (1,2,10,12). The effect of cisplatin treatment on the viability of representative clonal lines of the dnJun-expressing T98G cells is compared with that of an empty vector control line, T98GLHCX, in Fig.…”
Section: Dominant Negative C-jun Sensitizes Tumor Cells To Cisplatin mentioning
confidence: 97%
“…Phosphorylation of c-Jun at these sites greatly enhances the transactivation potential of the AP-1 binding sites (1)(2)(3)(4) and AP-1 regulated genes in vivo (5,11,12), and there is evidence suggesting roles for c-Jun phosphorylation in cellular transformation (1,2), inflammation (14), and apoptosis (15). The JNK/SAPK pathway is strongly stimulated in a dose-dependent manner by various DNA damaging treatments, including UV-C (5, 7-8), ionizing radiation (16), and alkylating agents such as N-methyl-NЈ-nitro-N-nitrosoguanidine (MNNG) (5), methylmethanesulfonate (MMS) (11), 1-␤-D-arabinofuranosylcytosine (Ara-C) (17), and hydrogen peroxide (18).…”
mentioning
confidence: 99%
“…A group of ATF-2 target genes have been identified that are involved in multiple biological phenomena. The target genes of c-Jun/ATF-2 heterodimers, which are implicated in growth control, include c-jun itself and interferon-␤ (van Dam et al, 1993;Falvo et al, 2000). The platelet-derived growth factor receptor ␣ gene, which is critical for proliferation of cytotrophoblasts, is an ATF-2 target and its expression level is decreased in the placenta of Atf-2 mutant mice (Maekawa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%